Multi-messenger emission characteristics of blazars - Gamble, Ronald; Forman, Jordan; Barnes, Amethyst; Srinivasaragavan, Gokul; Holt, Isiah; Jones, Marvin (Frontiers in Astronomy and Space Sciences, 2024)
Multi-messenger observations and theories of astrophysical objects are rapidly becoming a critical research area in the astrophysics scientific community. In particular, point-like objects such as BL Lacertae (BL Lac) objects, flat-spectrum radio quasars (FSRQs), and blazar candidates of uncertain type (BCUs) are of distinct interest to researchers studying the synchrotron, Compton, neutrino, and cosmic ray emissions sourced from compact objects. Notably, there is also much interest in the correlation between multi-frequency observations of blazars and neutrino surveys on source demographics. In this review, we look at such multi-frequency and multi-physics correlations of the radio, X-ray, and γ-ray fluxes of different classes of blazars from a collection of survey catalogs. This multi-physics survey of blazars shows that there are characteristic cross-correlations in the spectra of blazars when considering their multi-frequency and multi-messenger emission. In addition, a review of cosmic ray and neutrino emissions from blazars and their characteristics is presented.